Статистика туристичної сфери Волинської області - Бегун, Світлана Іванівна; Черчик, Лариса Миколаївна; Лажнік, Анжеліка; Begun, Svitlana; Cherchyk, Larysa; Lazhnik, Anzhelika (Економічний часопис ВНУ імені Лесі Українки, 2021)
У статті розглянуто динаміку основних кількісних (кількість суб'єктів туристичної діяльності; кількість туристичних путівок, реалізованих туроператорами та турагентами; кількість туроднів за реалізованими туроператорами та турагентами туристичними путівками; чисельність туристів, обслугованих туроператорами та турагентами; розподіл туристів за метою поїздки; показники кадрового забезпечення суб’єктів туристичної діяльності) та вартісних (дохід від надання туристичних послуг, операційні витрати, вартість туристичних путівок, реалізованих туроператорами та турагентами) показників туристичної сфери Волинської області. Визначено їх частку у відповідних показниках загалом по Україні. Виявлено основні передумови, які вплинули на стан розвитку туристичної сфери за період 2015-2019 років.

The article considers the dynamics of the main quantitative and cost indicators of the tourism sector of the Volyn region. Their share in the corresponding indicators as a whole across Ukraine is defined. The number of tourism entities in the Volyn region has increased slightly, mainly due to an increase in the number of travel agents – individuals. The number of tourist vouchers and tours sold by tour operators and travel agents has also increased, but at a much slower pace than in Ukraine. The same trend in terms of the number of tourists served by tour operators and travel agents. Most of them are residents of the Volyn region, more than 56% of whom go abroad, more than 30% travel in Ukraine, the rest are foreign guests. The purpose of the trip for a significant part of tourists is recreation and entertainment (97%). Indicators of staffing of tourism entities - legal entities and individuals are insignificant, 45 and 50 people, respectively. The dynamics of the call sign growth of domestic tourism indicates the formation of the internal culture of recreation, a return to national historical and cultural traditions. In addition, the development of domestic tourism creates additional jobs, expands opportunities for self-employment, ensures the development of new areas of economic activity, contributes to the economic and social strengthening of local communities. Despite the critical situation associated with economic crises, and now - with the pandemic and lockdown in our country and many countries, services are provided, their performance is quite high: in 2019 compared to 2015, despite a significant reduction in the number of tour operators, the number sold tourist vouchers increased, income from tourist services increased, The main preconditions that have affected the state of the tourism sector for the period 2015-2019 have been identified: increasing risks of disease, deteriorating health of the nation; low incomes of a significant part of the population and a high level of stratification of Ukrainian society; increasing the level of urbanization, urban population, reducing safe living space; environmental pollution, deterioration of the natural environment.
STATISTICS OF THE TOURIST SPHERE OF VOLYN REGION
Keywords: статистика; туризм; туристичні агенції; туристичні агенції; statistics; tourism; travel agencies; tour operators; 338.24